Relation of pretreatment sequence diversity in NS5A region of HCV genotype 1 with immune response between pegylated-INF/ribavirin therapy outcomes - de Queiroz, A. T. L.; Maracaja-Coutinho, V.; Jardim, A. C. G. [UNESP]; Rahal, Paula [UNESP]; de Carvalho-Mello, I. M. V. G.; Matioli, S. R. (Wiley-Blackwell Publishing, Inc, 2011)
Hepatitis C virus (HCV) infection frequently persists despite substantial virus-specific immune responses and the combination of pegylated interferon (INF)-alpha and ribavirin therapy. Major histocompatibility complex class I restricted CD8+ T cells are responsible for the control of viraemia in HCV infection, and several studies suggest protection against viral infection associated with specific HLAs. The reason for low rates of sustained viral response (SVR) in HCV patients remains unknown. Escape mutations in response to cytotoxic T lymphocyte are widely described; however, its influence in the treatment outcome is ill understood. Here, we investigate the differences in CD8 epitopes frequencies from the Los Alamos database between groups of patients that showed distinct response to pegylated alpha-INF with ribavirin therapy and test evidence of natural selection on the virus in those who failed treatment, using five maximum likelihood evolutionary models from PAML package. The group of sustained virological responders showed three epitopes with frequencies higher than Non-responders group, all had statistical support, and we observed evidence of selection pressure in the last group. No escape mutation was observed. Interestingly, the epitope VLSDFKTWL was 100% conserved in SVR group. These results suggest that the response to treatment can be explained by the increase in immune pressure, induced by interferon therapy, and the presence of those epitopes may represent an important factor in determining the outcome of therapy.
Keywords: Genotype 1; Hepatitis C virus; hepatitis; Immune response; NS5A